Nuisances, § 5. MACON, A COMPILATION OF THE ORDINANCES (S. Rose & Co. 1862) - (:unkn) unknown (General Publisher, 1862)
“SEC. 5. It shall not be lawful for any person to fire a gun, pistol, or any other fire arms, within three hundred yards of any house, except in cases of military parade; nor shall any person burn rockets, crackers, or any kind of fire works within the limits of the city. Any person so offending shall be fined in a sum not exceeding twenty dollars.”
--
Keywords: DISCHARGE